Combined heart–liver transplantation: Indications, outcomes and current experience() - Beal, Eliza W. (Transplant Rev (Orlando), 2016)
Combined heart–liver transplantation is a rare, life-saving procedure that treats complex and often fatal diseases including familial amyloidosis polyneuropathy and late stage congenital heart disease status-post previous repair. There were 159 combined heart–liver transplantations performed between January 1, 1988 and October 3, 2014 in the United States. A multitude of potential techniques to be used for combined heart and liver transplant including: orthotopic heart transplant (OHT) and orthotopic liver transplant (OLT) on full cardiopulmonary bypass (CPB), OHT with CPB and OLT with venovenous bypass (VVB), OHT with CPB and OLT without VVB, enbloc technique and sequential transplantation. Outcomes of combined heart–liver transplant have been demonstrated to be comparable to outcomes of isolated heart and isolated liver transplant. The liver graft may provide some tolerance of other allografts © 2016 Elsevier Inc. All rights reserved.